Brain‐derived neurotrophic factor Val66Met polymorphism association with antidepressant efficacy: A systematic review and meta‐analysis. (18th September 2014) - Yan, Tingting; Wang, Lijuan; Kuang, Weihong; Xu, Jiajun; Li, Suping; Chen, Jie; Yang, Yanchun
Abstract Introduction Previous studies of the association of the brain‐derived neurotrophic factor (BDNF) Val66Met polymorphism with antidepressant efficacy are inconsistent. Thus, we conducted a systematic review and meta‐analysis. Methods We searched MEDLINE, PubMed, EMBASE, and Chinese Databases (Biomedical Literature Database, National Knowledge Infrastructure, Weipu, and WanFang) up to March 2013 for relevant studies (584 retrieved, 16 met inclusion criteria). We conducted six comparisons for both response and remission rates for three genotypes in Caucasians and Asians (4 weeks or ≥6 weeks; selective serotonin reuptake inhibitors [SSRIs], serotonin‐noradrenaline reuptake inhibitors, or mixed antidepressants). Results Met carriers had a better response rate than Val/Val. In Asians, the Met carrier was positively associated with response rate (odds ratio; 95% confidence interval: 1.48; 1.02–2.14) in the SSRI group (1.81; 1.10–2.97) and with treatments ≥6 weeks. Met/Val showed a positive association with the response rate versus homozygotes (1.60; 1.20–2.13) and for ≥6 weeks (mixed antidepressant, 1.36; 1.04–1.77; SSRI, 1.55; 1.11–2.17). There was a weak effect of Met/Val versus Val/Val in response to SSRIs (mixed time, 2.07; 1.48–2.89; ≥6 weeks, 2.25; 1.53–3.32). For remission, Met/Val was better than the homozygotes (1.71; 1.09–2.68, Asians, SSRIs only). Discussion Our meta‐analysis confirms the effects of the BDNF polymorphism on SSRI response in Asians. This effect may be dependent on ethnic origin because BDNF had a lesser influence on response in mixed race studies. Antidepressants were more effective in groups with a treatment duration ≥6 weeks. Thus, future investigators should carefully consider their outcome observation end point.